Data Science with SQL Server Quick Start Guide: Integrate SQL Server with Data Science - Sarka, Dejan (Packt Publishing, Limited, 2018)
SQL Server started to fully support data science only with its last two editions. If you are a professional from both worlds, SQL Server and data science, and interested in using SQL Server and Machine Learning Services for their projects, then this is the ideal book for you.